SISTEM INFORMASI PELAYANAN ADMINISTRASI KEPENDUDUKAN DESA CIKEMBULAN BERBASIS WEB - Heru Winarno; Luluk Harjanto; Tati Sukmawati; Fani Munawaroh (Institut Teknologi dan Bisnis (ITB) Swadharma, 2021)
The internet as a transmitter of information on its existence has now become a necessity, including in Indonesia. The government agency at the lowest level is the Kelurahan Office, which interacts directly with the community. Its authority includes regulating, managing resources in government at the village level and is obliged to carry out population administration as a form of service to the community. At the Cikembulan Sub-District Office, the processing of population data is carried out semi-computerized using Microsoft Excel and Microsoft World. So that when making files or letters, errors often occur due to human error. The purpose of this study is to design a web-based information system for population administration services in Cikembulan village, to improve its services. The methodology used is field research, with observation and interview data collection techniques. The results of the system is that population administration can run smoothly